2018
DOI: 10.17159/sajs.2018/20170254
|View full text |Cite
|
Sign up to set email alerts
|

Psychrophiles: Ecological significance and potential industrial application

Abstract: The bulk of earth’s biosphere is cold 5 °C that sustains a broad diversity of microbial life by triggering physiological response(s) to ensure survival in cold and frozen ecosystems. The strategy of adaptation to cold environments includes changes in membrane composition and induction of a set of specific cold-active proteins, polyunsaturated lipids and exopolysaccharides. These adaptive features provide an enormous natural reservoir of enzymes that function effectively in cold environments, and these coldacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…The study of psychrophilic bacteria as new tools in pharmaceuticals is especially promising. At the moment, several promising psychrophilic strains have been discovered that are producers of new highly active antimicrobial compounds [ 31 ], such as antarticin-NF3, synthesized by the Antarctic bacterium Pseudoalteromonas [ 32 ], and the bacteriocins of Pseudomonas antarctica PAMC 27494 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of psychrophilic bacteria as new tools in pharmaceuticals is especially promising. At the moment, several promising psychrophilic strains have been discovered that are producers of new highly active antimicrobial compounds [ 31 ], such as antarticin-NF3, synthesized by the Antarctic bacterium Pseudoalteromonas [ 32 ], and the bacteriocins of Pseudomonas antarctica PAMC 27494 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perchrophils and psychrotrophs are phylogenetically diverse groups and include various families of bacteria and archaea [ 31 ]. This study showed that the microbial communities of the Walter quarry are represented by the families Ruminococcacea, Lachnospiraceae, Burkholderiaceae, Bacteroidaceae, Geodermatophilaceae, Bacillaceae, Rhizobiaceae, Planctomycetes, Opitutaceae, Moraxellaceae, and Mycobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, such microorganisms are capable of fulfilling multiple and diverse roles in such cold and harsh environments. They can enhance the quality of the soil structure, fix nitrogen, or break down organic matter for plants to absorb or deteriorate pollutants [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…(i) Increased fluidity of cell membranes (ii) e freezing point of the aqueous phase in the cytoplasm decreased (iii) Macromolecules with enhanced stability (iv) Under the effects of cold shock and cold acclimation, the reaction protein of cells to temperature decreases (v) Peroxidase, catalase, redox, and superoxide dismutase protect reactive oxygen species (vi) Whether the catalytic efficiency is maintained under cold stress and under cold stress [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%